Laboratory manual in microbiology - Tabo, Norbel A. (Manila, Philippines : Rex Book Store, 2005)
The Laboratory manual in microbiology (updated edition) is designed for students in taking their first course in microbiology. It provides up-to-date activities that demonstrate the basic concepts to microbiology as well as the importance of microorganisms in the environment. It aims to strengthen the students' grasp of the fundamentals of microbiology introduced in the lecture.- - Preface.
Part I Activity - Basic microbiology -- Part II Activity - Applied microbiology -- Part III Activity - Parasitology.
Includes bibliographical references.
Keywords: MICROBIOLOGY